Identification and Prioritization of Factors Affecting the Marketing of Solar Energy Production Equipment Based on a Combined Approach of Content Analysis and Fuzzy Delphi - Rezvanian, Mohammad Hossein; Haghshenaskashani, Farideh; Karimizand , Mehdi (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The aim of this research is to identify and prioritize the factors affecting the marketing of solar energy production equipment based on a combined approach of content analysis and fuzzy Delphi. Methodology: In this study, the purposive snowball sampling method was used to gather opinions from 15 experts and professors from the Iranian Renewable Energy Association, the Renewable Energy and Energy Efficiency Organization of Iran, and the Solar Energy Committee of the Vice Presidency for Science and Technology. The data analysis process was conducted in two stages: identifying the influencing factors through interview tools and content analysis, and screening and prioritizing these factors using questionnaire tools and the fuzzy Delphi method. Findings: The results of the study indicated that government policies hold the highest priority among the factors affecting the marketing of solar energy production equipment. Conclusion: Following this, the factors in order of priority are brand/product awareness, distrust in solar technology and equipment, the local lifestyle of each region, remarketing, creating added or unique value for the product, market research, defining and identifying the audience and target market, aiding in sales growth, climate change and the necessity of environmental preservation, optimizing marketing through social media, business survival in a competitive market, creativity in marketing, utilization of digital capabilities, cost reduction, improving customer experience and creating a memorable product image, building trust through social proof, the general public’s benefit from the social and environmental advantages of marketing solar equipment, and the need for a communication channel to inform customers.